Performance and presentation production elements - Miklavcic, Beth; Miklavcic, Jimmy (Conference on High Performance Networking and Computing: Proceedings of the 2006 ACM/IEEE conference on Supercomputing; 11-17 Nov. 2006, 2006)
Beth Miklavcic will give a Power Point Presentation focusing on video images comparing sent streams that work and sent streams that detract from meetings. Formatting of streams for performances will also be shown. Discussion of detail and point of view of various shots will be demonstrated for the best results during a performance over the grid. The psychology of camera angles and the project of self-image will be discussed.Jimmy Miklavcic will give a presentation of audio examples focusing on a variety of audio problems that can arise for example etiquette when entering a meeting and during a meeting. Jimmy will cover the best audio equipment set up and he will propose possible approaches for improving the audio tools currently available within the access grid software, including a discussion of the newest microphones used for best audio results. Performance subjects such as echo canceling and distortion levels will also be discussed.